Fc receptor is not required for inducing antibodies but plays a critical role in conferring protection after influenza M2 vaccination - Lee, Yu-Na (Blackwell Science Inc, 2014)
The ectodomain of matrix protein 2 (M2e) of influenza virus is considered a rational target for a universal influenza A vaccine. To better understand M2e immune-mediated protection, Fc receptor common γ chain deficient (FcRγ(−/−)) and wild-type mice were immunized with a tandem repeat of M2e presented on virus-like particles (M2e5x VLP). Levels of M2e-specific antibodies that were induced in FcRγ(−/−) mice after immunization with M2e5x VLP were similar to those in wild-type mice. In addition, M2e antibodies induced in FcRγ(−/−) mice were found to be equally protective as those induced in wild-type mice. However, M2e5x VLP-immunized FcRγ(−/−) mice were not well protected, as shown by severe weight loss, higher lung viral titres and interleukin-6 inflammatory cytokine production upon influenza virus challenge compared with M2e5x VLP-immunized wild-type mice. Importantly, FcRγ(−/−) mice that were immunized with inactivated influenza virus induced haemagglutination inhibition activity and were well protected without a significant weight loss. Interestingly, interferon-γ-producing CD4 T and CD8 T cells were found to be prevalent in lungs from M2e5x VLP-immunized FcRγ(−/−) mice, which appeared to be correlated with a faster recovery after infection. These results indicate that Fc receptors play a primary role in conferring M2e-specific antibody-mediated protection whereas T cells may contribute to the recovery at later stages of infection.